Current Status of Endoscopic Surgery in Japan: The 15th National Survey of Endoscopic Surgery by the Japan Society for Endoscopic Surgery. Issue 2 (26th December 2021) - Shiroshita, Hidefumi; Inomata, Masafumi; Akira, Shigeo; Kanayama, Hiroomi; Yamaguchi, Shigeki; Eguchi, Susumu; Wada, Norihito; Kurokawa, Yukinori; Uchida, Hiroki; Seki, Yosuke; Ieiri, Satoshi; Iwazaki, Masayuki; et al.
Abstract: In Japan, the first endoscopic surgery, a laparoscopic cholecystectomy, was performed in 1990. Since then, operative procedures have been standardized, and the safety and efficacy of endoscopic surgery have been evaluated. In accordance with the social acceptance of endoscopic surgery as a less invasive type of surgery, the number of endoscopic procedures performed has increased in all surgical domains. The Japan Society for Endoscopic Surgery (JSES) has played an important role in the development of endoscopic surgery in Japan. Notably, a technical skills certification system for surgeons was established by the JSES to train instructors on how to teach safe endoscopic surgery. Furthermore, the JSES has conducted a national survey every 2 years. In 2019, 291, 792 patients underwent endoscopic surgery in all surgical domains, such as abdominal, thoracic, mammary and thyroid gland, cardiovascular, obstetrics and gynecology, urologic, orthopedic, and plastic surgery. The 15th National Survey of Endoscopic Surgery conducted by the JSES demonstrated the status of laparoscopic surgery in Japan in 2018–2019.